China’s state-led international port development: Challenges for port states - Christopher J. Watterson; Jean-Annet de Saint Rapt; Eunha Yun (Marine Policy, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Analysis of CMIP6 atmospheric moisture fluxes and the implications for projections of future change in mean and heavy rainfall - Ian G. Watterson; Richard J. Keane; Martin Dix; Tilo Ziehn; Timothy Andrews; Yongming Tang (International Journal of Climatology, 2021)
Motivated by the wide range of projections of regional rainfall (or precipitation, pr) based on the CMIP5 ensemble of global climate models, we investigate the atmospheric moisture budget of idealized rising‐CO 2 (1pctCO2) simulations from 10 models submitted to CMIP6. We use the new CMIP6 standard variables, the vertically integrated eastward and northward moisture flux, and provide a multi‐model assessment of these, their convergence (conv), along with water vapour path (prw). Seasonal climatologies of a 20‐year base climate for pr, prw, flux, and conv match well those from the ECMWF's Reanalysis 5. In addition, composites ‘H’ of quantities for months in the top decile of monthly rainfall, calculated at each model grid point, produce a field of heavy rainfall, on average double that of the mean. Spatial correlation coefficients ( r ) between the pr and conv fields are typically .7 in each season. This rises to .9 for the corresponding H fields, due to the important link between moisture convergence and heavy rainfall. Fields of standardized change (Δ), or change per degree of global warming, were calculated. The ensemble‐mean Δpr is only weakly correlated with the base climate pr, and likewise for conv. However, the prw change is highly correlated with the base prw, pointing to the importance of the “thermodynamic” change in that variable. Globally, the net Δconv is highly correlated with Δpr, around .9. This rises to .95 for the heavy‐rain composites. Relationships between changes in pr and other components hold at grid points also, when the individual model results are correlated. Clearly, there is a dependence in the change in pr with that in conv, particularly for heavy rainfall. Assessment of a larger ensemble from CMIP6, using the new flux variables, would improve the evaluation of these processes, and potentially allow more confident projections in future rainfall changes.

Genetic knockout of myosin light chain kinase (MLCK210) prevents cerebral microhemorrhages and attenuates neuroinflammation in a mouse model of vascular cognitive impairment and dementia - David J. Braun; Adam D. Bachstetter; Tiffany L. Sudduth; Donna M. Wilcock; D. Martin Watterson; Linda J. Van Eldik (GeroScience, 2019)

A deep-sea community, including Lophelia pertusa, at unusually shallow depths in the western North Atlantic Ocean off northeastern Florida - Steve W. Ross; Sandra Brooke; Andrea M. Quattrini; Mike Rhode; J. Carter Watterson (Marine Biology, 2015)

Target Engagement Analysis and Link to Pharmacodynamic Endpoint for a Novel Class of CNS-penetrant and Efficacious p38α MAPK Inhibitors - Adam D. Bachstetter; D. Martin Watterson; Linda J. Van Eldik (Journal of Neuroimmune Pharmacology, 2014)

Detrimental effects of acute nicotine on the response-withholding performance of spontaneously hypertensive and Wistar Kyoto rats - Gabriel J. Mazur; Gabriel Wood-Isenberg; Elizabeth Watterson; Federico Sanabria (Psychopharmacology, 2014)

The influence of air–sea interaction on the Madden–Julian Oscillation: the role of the seasonal mean state - I. G. Watterson; J. Syktus (Climate Dynamics, 2007)

Discovery of new chemical classes of synthetic ligands that suppress neuroinflammatory responses - D. Martin Watterson; Jacques Haiech; Linda J. Van Eldik (Journal of Molecular Neuroscience, 2002)

Phosphorylation of kinase-related protein (telokin) in tonic and phasic smooth muscles - Mikhail A. Krymsky; Dmitry S. Kudryashov; Vladimir P. Shirinsky; Thomas J. Lukas; D. Martin Watterson; Alexander V. Vorotnikov (Journal of Muscle Research and Cell Motility, 2001)

Effect of air cavities on the dose delivered to the lung during high-dose brachytherapy - Richard M. Ambrosi; John I. W. Watterson; Tom Nam; Rex J. Keddy (Biological Trace Element Research, 1999)